Auctions for allocation of offshore wind contracts for difference in the UK. (March 2020) - Welisch, Marijke; Poudineh, Rahmatallah
Abstract: The contract for difference (CfDs) auctions are the cornerstone of the UK electricity sector's decarbonization policy and were introduced as part of the Electricity Market Reform in 2013. The CfD auctions appear to have been successful in achieving low bids for low-carbon technologies, especially offshore wind power. However, the design of the auction increases the probability of speculative bidding, while the one-shot nature of the auction prevents bidders from learning and from utilizing information efficiently. We show that implementing a stringent non-delivery penalty to induce truth telling can improve deployment rate without increasing support costs. Moreover, by holding regularly scheduled (annual, for example) auctions, information on technology cost decreases can be better incorporated into the bids, lowering investor uncertainty and thus having a positive effect on support costs. Highlights: This paper analyses auctions for allocation of offshore wind CfD contract in the UK. We argue that CfD auction design increases possibility of speculative bidding. We show a stringent penalty improves deployment rate without raising support costs. Also, by holding regular auctions investors' uncertainty and costs can be lowered.